PERANCANGAN USULAN TATA LETAK FASILITAS PABRIK DI XYZ - Riadi, Sugeng; Hasibuan, Rizki (Computer Science and Industrial Engineering, 2023)
A good layout ensures efficient material flow, short material transfer distances and minimal material handling costs so operators can work optimally. To deliver goods to the Shifting Lever line which is 23 meters away and takes 53 seconds and must pass through several departments that should not be related to material handling. The current layout is not good because the distance between the storage room and the production area is too far apart and results in a lot of wasted time delivering goods and even longer waiting times. Activity Relationship Chart (ARC) will be used in planning the linkages between each group of interrelated activities. And combined with the method for the Blocplan Algorithm to calculate the degree of closeness between each department. The total material handling displacement distance is calculated as 48,815 meters per month and 585,780 meters per year and causes a total OMH cost of IDR 12,545,455 per month and IDR 150,545,460 per year. and incur OMH costs of IDR 8,828,413 per month and IDR 105,940,956 per year so that the new layout analysis reduces the material handling mileage by 173,547 meters per year and OMH by IDR 44,604,504 per year, or 29.6% per year.